Resiko Bisnis, Profitabilitas, Nilai Perusahaan, Perataan Laba Sebelum dan Saat Pandemi Covid-19 pada Sektor Barang Konsumsi - Fitri Ella Fauziah; Murharsito (Journal of Trends Economics and Accounting Research, 2024)
The objective of this study is to determine whether there are differences in company risk, profitability, company value and income smoothing before and during the Covid-19 pandemic. This research is quantitative research with the research population including consumer goods companies listed on the IDX and the research sample selection used purposive sampling. Data analysis used the sample difference test t-test and paired Wilcoxon test. The research findings are that profitability has a different test value of 0.017, which means that it has a difference before and during the Covid-19 epidemic, but the variables of company value, business risk and income smoothing each have a different test value of 0.266; 0.601 and 0.218 which means there is no difference before and during the Covid-19 epidemic.